Increasing Prepregnancy Obesity Is Associated with Large-for-Gestational Age Infants Among a Diverse, Contemporary Cohort (P11-018-19). (13th June 2019) - Nichols, Amy; Hedderson, Monique; Xu, Fei; Widen, Elizabeth
Abstract: Objectives: The Institute of Medicine (IOM) gestational weight gain (GWG) recommendations do not differentiate by severity of obesity. Among a large, diverse cohort of women with obesity, we assessed gestational weight gain and neonatal size outcomes between prepregnancy obesity classes. Methods: Electronic health records from 25, 017 women with obesity who delivered singleton term births (37-42 weeks) at Kaiser Permanente Northern California between 2008–2013 were abstracted. We examined associations between BMI obesity class (class 1 30–34.9 kg/m 2 ; class 2 35–39.9 kg/m 2 ; class 3 ≥ 40 kg/m 2 ), total GWG, adherence to IOM recommendations (below, within, or above), infant birthweight and large-for-gestational age (LGA,  > 90 th percentile for weight) using analysis of variance or chi 2 . Multivariable linear and logistic regression models were used to examine associations between obesity class, total GWG, and neonatal size, adjusting for maternal height, infant sex, race/ethnicity, parity, gestational age at delivery, and total GWG in neonatal models. Results: Before pregnancy, 60.9% of women had class 1 obesity, 24.6% class 2, and 14.5% class 3. Adherence to IOM recommendations varied by obesity class ( P  < 0.001); overall, a majority (59.0%) of women showed excessive GWG (64.3% class 1; 53.7% class 2; 45.7% class 3) with a smaller proportion (21.0%) gaining within IOM recommendations (20.9% class 1; 21.5% class 2; 20.5% class 3). In adjusted models, compared to women with class 1 obesity, estimated total GWG was 1.89 kg lower among women with class 2 obesity ( P  < 0.001), and 3.4 kg lower among women with class 3 obesity ( P  < 0.001). A total of 3933 neonates were born LGA (14.4% class 1; 16.9% class 2; and 19.5% class 3). In adjusted models, compared to women with class 1 obesity, neonates born to women with class 2 or class 3 obesity were heavier (class 2: b = 58.3g, 95% CI (45.1, 71.5), P  < 0.001; class 3: b = 121.5g, 95% CI (105.1, 137.8), P  < 0.001) and at higher risk for LGA infants (class 2 AOR 1.50, CI: 1.28, 1.77; P  < 0.001; class 3 AOR 2.38, 95% CI: 2.01, 2.82; P  < 0.001). Conclusions: Prepregnancy class 2 and class 3 obesity were associated with lower gestational weight gain, but higher infant birthweight and risk for LGA. The optimal range of maternal weight gain that balances risk for mothers and infants may vary by severity of obesity. Funding Sources: Kaiser Permanente Community Benefit Grant to Monique Hedderson, PhD.